COMBATTING CORRUPTION IN INDONESIAN REGIONAL GOVERNANCE: STRATEGIES, CHALLENGES, AND PATHWAYS TO STABILITY - Wijanarko, Dwi Seno (Jurnal Pembaharuan Hukum, 2024)
This study investigates initiatives aimed at the local government level to end criminal acts of corruption. The persistence challenge of corruption in Indonesia especially within the regional governance still happening despite extensive anti-corruption initiatives in the country. By examining the multifaceted modus operandi across the local government it will uncovering the menacing threat that corruption poses to the stability of the regional governance, if not, the country. Analyzing how well local governments use procedures and techniques to combat corruption is the primary goal of their research.  The study results offer a comprehensive understanding of the difficulties and roadblocks encountered in attempts to end corruption on a regional scale. Furthermore, this study also finds contributing elements that can boost anti-corruption initiatives' efficacy. The anticipated outcomes are anticipated to enhance comprehension of the mechanisms involved in eliminating corruption at the local government level and offer a foundation for enhancing policies and putting them into effect.